Publicaciones científicas de Costa Rica en el Science Citation Index: análisis bibliométricos del trienio 1999-2001 - Lomonte, Bruno (Universidad de Costa Rica, 2002)
This study analyzed the publications of authors from Costa Rican institutions that were included in the Science Citation Index (SCI) during 1999-2001. Out of the 722 references detected, distributed in 328 journals, 90.7% corresponded to original research articles. The total productivity figures showed a moderately increasing trend, both in absolute and population-adjusted terms, in concordance with previous data recorded for the period 1980-1998. The contribution of Revista de Biología Tropical to these figures corresponded to 10.0%, 8.9%, and 19.1%, for the years 1999, 2000, and 2001, respectively. The subject distribution of articles followed a similar pattern to that described for 1980-1998, with a predominance of biomedical (33.3%) and biological (27.5%) sciences, followed by agronomical (15.5%) sciences, chemistry (13.6%), physics (5.0%), geological sciences (3.6%), and mathematics (1.5%). Citation analyses for individual publications (up to July 15, 2002) revealed that only 45.2% of the articles had been cited at least once. The ten most cited references were analyzed, varying from 26 to 114 citations. The average citation per article was 2.60, and the average number of authors per article was 2.92. In agreement with data from 1980-1998, the University of Costa Rica appeared as the institution with highest productivity of SCI publications during 1999-2001, with a contribution of 50.0%. The percentage of publications performed without the participation of foreign co-authors showed a change in its decreasing trend of 1980-1998, stabilizing near the range of 25-30% during the period 1999-2001.